The Production Process of 3D Film and Animation ‘The City of Paper Folding’ - Chen, Xushang; Yuan, Mingjing (International Journal of Computer Science and Information Technology, 2024)
The design of three-dimensional animation is based on multimedia computer, which integrates literature, aesthetics, dynamics, film art and other disciplines. Practical operation requires cooperation of many people, bold innovation and continuous improvement. With the enhancement of science and technology and the support of software, three-dimensional design, a new design method, has been widely used in many fields, such as architecture, industry, mould and so on. The following is the process of collecting and arranging three-dimensional design for you. Interested can see. At present, most of the architectural animation is divided into three major steps: early stage of animation design.3D animation pre-production: refers to the use of computer before the formal production of animation planning and design, mainly including: script creation, sub-lens script creation, modeling design, scene design.3D animation pre-production: refers to the use of computer before the formal production of animation planning and design, mainly including: script creation, sub-lens script creation, modeling design, scene design.